The highest intensity and the shortest duration permitting attainment of maximal oxygen uptake during cycling: effects of different methods and aerobic fitness level - Caputo, F.; Denadai, B. S. (European Journal of Applied Physiology, 2008)
The aims of this study were: (1) to verify the validity of previous proposed models to estimate the lowest exercise duration (T LOW) and the highest intensity (I HIGH) at which VO2max is reached (2) to test the hypothesis that parameters involved in these models, and hence the validity of these models are affected by aerobic training status. Thirteen cyclists (EC), eleven runners (ER) and ten untrained (U) subjects performed several cycle-ergometer exercise tests to fatigue in order to determine and estimate T LOW (ET LOW) and I HIGH (EI HIGH). The relationship between the time to achieved VO2max and time to exhaustion (T lim) was used to estimate ET LOW. EI HIGH was estimated using the critical power model. I HIGH was assumed as the highest intensity at which VO2 was equal or higher than the average of VO2max values minus one typical error. T LOW was considered T lim associated with I HIGH. No differences were found in T LOW between ER (170 ± 31 s) and U (209 ± 29 s), however, both showed higher values than EC (117 ± 29 s). I HIGH was similar between U (269 ± 73 W) and ER (319 ± 50 W), and both were lower than EC (451 ± 33 W). EI HIGH was similar and significantly correlated with IHIGH only in U (r = 0.87) and ER (r = 0.62). ET LOW and T LOW were different only for U and not significantly correlated in all groups. These data suggest that the aerobic training status affects the validity of the proposed models for estimating I HIGH.